2000
DOI: 10.1046/j.1365-3040.2000.00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel multiple environmental factor‐responsive 1‐aminocyclopropane‐1‐carboxylate synthase gene, NT‐ACS2, from tobacco

Abstract: Many abiotic environmental factors elicit the production of stress‐ethylene in higher plants. To elucidate the molecular mechanisms underlying the regulation of stress‐ethylene production and the physiological roles played by stress‐ethylene in stress responses of plants, we studied the gene expression of ACC synthase in tobacco plants that had been subjected to environmental stresses. Four new tobacco ACC synthase cDNA fragments, NT‐ACS2, NT‐ACS3, NT‐ACS4 and NT‐ACS5, were identified and sequenced. It was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 93 publications
4
31
0
1
Order By: Relevance
“…The large increase in ACC observed here in response to EEE has been described in other studies and referred to as stress ethylene, an early response that amplifies programmed cell death signals (Ge et al, 2000;Overmyer et al, 2000;Tuominen et al, 2004). Our results show that LSD1 suppresses an ethylene/ ROS-dependent programmed cell death pathway that requires the functions of EDS1 and PAD4 (Figure 9).…”
Section: Role Of Ethylene In Eee-induced Programmed Cell Deathsupporting
confidence: 86%
See 1 more Smart Citation
“…The large increase in ACC observed here in response to EEE has been described in other studies and referred to as stress ethylene, an early response that amplifies programmed cell death signals (Ge et al, 2000;Overmyer et al, 2000;Tuominen et al, 2004). Our results show that LSD1 suppresses an ethylene/ ROS-dependent programmed cell death pathway that requires the functions of EDS1 and PAD4 (Figure 9).…”
Section: Role Of Ethylene In Eee-induced Programmed Cell Deathsupporting
confidence: 86%
“…Previously, it was reported that ROS and ethylene regulate photosynthesis (Kays and Pallas, 1980;Asada, 1999;Karpiń ski et al, 1999) and that ethylene potentiates the oxidative burst (Ge et al, 2000;de Jong et al, 2002;Tuominen et al, 2004). Therefore, we measured levels of hydrogen peroxide (H 2 O 2 ) and 1-aminocyclopropane-1-carboxylate (ACC), which is the immediate biosynthetic precursor of ethylene and a reliable marker of ethylene levels in the plant (Adams and Yang, 1979).…”
Section: Eee-induced Local and Systemic Programmed Cell Death Dependsmentioning
confidence: 99%
“…Total RNA of 15 mg was loaded on each lane for electrophoresis. RNA transfer and cross-linking onto a nylon membrane (Hybrid N 1 ; Amersham) was as described (Sambrook et al, 1989;Ge et al, 2000). The probe of TaRAN1 cDNA was labeled with [ 32 P]dCTP (China Isotope).…”
Section: Rna Gel Blots and Rt-pcr For Gene Expression Analysismentioning
confidence: 99%
“…Total RNA electrophoresis and the programs of the RNA transferred and cross-linked onto a nylon membrane (Hybrid N 1 ; Amersham, Buckinghamshire, UK) were performed as described by Sambrook et al (1989) and Ge et al (2000). Total RNA of 15 mg was loaded on each lane.…”
Section: Rna Gel-blot Analysismentioning
confidence: 99%